Characterization of reading processes in Brazilian adolescents: development of criteria for identifying students at risk for dyslexia - de Assumpção Victorio, Renata Pires Sena; Germano, Giseli Donadon (Frontiers in Psychology, 2025)
IntroductionReading processes in Brazilian pre-adolescent and adolescent students are scarcely investigated, and it is essential to identify gaps and possible dyslexic students that have not yet been determined. Therefore, the objective of this study was to characterize the reading processes in adolescents and develop criteria to identify Brazilian students at risk for dyslexia in middle school.MethodsTwo hundred six students participated in the study, divided into four groups: 55 students (6th grade), 54 students (7th grade), 46 students (8th grade), and 51 students (9th grade). Initially, they were assessed collectively in the Evaluation of the Reading Processes Test. Criteria were developed, and the students were classified in relation to their reading performance as no risk, low risk (LR) and high risk (HR) for dyslexia. Only students who presented low or high risk were assessed individually, that is, 84 students. These were evaluated separately and classified in relation to accuracy and reading speed, meeting the criteria for risk for dyslexia. Finally, they were classified into phonological, visual and undefined profiles.ResultsThe collective phase revealed 27.3% LR and 12.7% with HR in GI, 29.6% with LR and 25.9% with HR in 7th grade, 23.9% with LR and 13% with HR in 8th grade, and 23.5% with LR and 5.9% with HR in 9th grade. As for profiles, 34.6% met the criteria for phonological profile, 23.8% for visual profile, 2.4% for mixed profile, and 39.3% of students did not fit the established profile criteria.ConclusionAssessments are necessary for this population, as evidenced by the indication of students at risk for dyslexia who have not yet been diagnosed. Finally, the study reinforces the idea of the heterogeneous nature of dyslexia in pre-adolescent and adolescent students.